Comprehensive Physiology 2018
DOI: 10.1002/cphy.c170041
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transport Across the Mammalian Intestine

Abstract: The small intestine mediates the absorption of amino acids after ingestion of protein and sustains the supply of amino acids to all tissues. The small intestine is an important contributor to plasma amino acid homeostasis, while amino acid transport in the large intestine is more relevant for bacterial metabolites and fluid secretion. A number of rare inherited disorders have contributed to the identification of amino acid transporters in epithelial cells of the small intestine, in particular cystinuria, lysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 343 publications
4
119
0
2
Order By: Relevance
“…As far as ATB 0,+ is concerned, data of transport analysis are fully in agreement with the immunocytochemical staining which showed a strong positivity of the protein at plasma membrane at the apical side. As far as the biologiocal role of this transporteer, it has been suggested that ATB 0,+ is expressed at places where the body interfaces with microbes, such as lung and colon and it may be involved in reducing available nutrients to bacteria [14]. Accordingly, the transporter is upregulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as ATB 0,+ is concerned, data of transport analysis are fully in agreement with the immunocytochemical staining which showed a strong positivity of the protein at plasma membrane at the apical side. As far as the biologiocal role of this transporteer, it has been suggested that ATB 0,+ is expressed at places where the body interfaces with microbes, such as lung and colon and it may be involved in reducing available nutrients to bacteria [14]. Accordingly, the transporter is upregulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the biologiocal role of this transporteer, it has been suggested that ATB 0,+ is expressed at places where the body interfaces with microbes, such as lung and colon and it may be involved in reducing available nutrients to bacteria [14]. Accordingly, the transporter is upregulated in inflammatory states, such as ulcerative colitis, Crohn's disease and colon cancer [14]. Moreover, genome-wide association studies has been recently identified ATB 0,+ (SLC6A14) as a genetic modifier of lung disease severity in cystic fibrosis, providing a mechanism by which it regulates Pseudomonas aeruginosa attachment to human bronchial epithelial cells [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Broer, both renal and intestinal LPI phenotypes are explained by the presence of the sole system y+L transporter in the basolateral membranes of these tissues ; indeed, the lack of a functional y+LAT1 consequent to SLC7A7 mutations is realistically the reason for the impaired absorption‐reabsorption of cationic amino acids, and, in turn, for the low plasma levels of arginine and other cationic amino acids in LPI patients. Our study of arginine transcellular fluxes in polarized layers of Caco‐2 cells confirms that system y + L in this model is operative at the basolateral side, blowing out arginine in exchange with leucine plus sodium.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, the amount of PPA produced by gut bacterial metabolism of phenylalanine will be dependent on total numbers of gut bacteria harboring the reductive pathway genes and the availability of the substrate phenylalanine. Free phenylalanine in diet is absorbed mostly in the small intestine (59), and only a small fraction reaches the lower gastrointestinal tract. A large portion of phenylalanine available to gut bacteria in the large intestine is derived from proteolytic degradation of proteins by gut bacteria, which releases free phenylalanine or phenylalanine-containing peptides (60).…”
Section: Discussionmentioning
confidence: 99%